Expert Opinion for Defining a Severe Bleeding Phenotype to Guide Prophylaxis in Patients with Nonsevere Hemophilia - Pfrepper, Christian; Ettingshausen, Carmen Escuriola; Klamroth, Robert; Oldenburg, Johannes; Olivieri, Martin (Hämostaseologie, 2024)
Prophylaxis is the standard of care for patients with severe hemophilia, patients with moderate hemophilia, or those with another congenital bleeding disorder that is associated with a severe bleeding phenotype and/or a high risk of spontaneous life-threatening bleeding. Patients with nonsevere hemophilia (factor VIII [FVIII] ≥ 1%) may also have a bleeding phenotype that requires prophylaxis. To date, however, there are no clear criteria as to when prophylaxis is indicated in these patients. Also, the term “severe bleeding phenotype (SBPT)” is neither included in the definitions of the International Society on Thrombosis and Haemostasis (ISTH) nor specified in the World Federation of Hemophilia (WFH) guidelines. Based on our personal experience and available evidence, we propose the criteria we use to define an SBPT and when we consider offering prophylaxis in patients with nonsevere hemophilia. Our proposals can be the basis for discussions in the community about the assessment of SBPT and the initiation of prophylaxis in patients with nonsevere hemophilia without inhibitors.
Keywords: nonsevere hemophilia; moderate hemophilia; severe bleeding phenotype; prophylaxis; expert opinion